Determination and correlation of anti-Neospora caninum antibodies in dairy cattle and dogs from the microregion of Fernandópolis, state of São Paulo, Brazil (Research, Society and Development, 2022)
Neosporosis is a parasitic disease that affects a variety of mammals, including cattle, which when infected can present as main symptoms reproductive disorders that lead to significant economic losses for dairy and beef cattle. The aim of this study was to determine and compare the occurrence of anti-Neospora caninum antibodies in cattle and dogs, evaluating whether there was correlation. The sera were collected through venocentesis of 87 animals, 75 dairy cattle and 12 dogs from 5 rural properties in Fernandópolis / SP microregion, after being deposited directly in tubes without anticoagulant and stored at -20º C they were processed by indirect fluorescent-antibody test (IFAT). The owners answered a questionnaire to collect information about the animals and the property that allowed the characterization of the place. The prevalence in cattle was 13.33% and in dogs 25%, and no correlation was observed between infected dogs and the presence of the disease in the herd.